Managing, Inducing, and Preventing Regime Shifts: A Review of the Literature - Ngo Van Long (Center for Economic Studies and ifo Institute (CESifo), 2019)
How do economic agents manage expected shifts in regimes? How do they try to influence or prevent the arrival of such shifts? This paper provides a selective survey of the analysis of regime shifts from an economic view point, with particular emphasis on the use of the tech-niques of optimal control theory and differential games. The paper is organized as follows. Section 2 gives an overview of the concepts of regime shifts, thresholds, and tipping points. Section 3 shows how unknown tipping points affect the optimal current policy of decision makers, with or without ambiguity aversion. Section 4.s focus is on political regime shifts in a two-class economy: how the elite may try to prevent revolution by using policy instruments such as repression, redistribution, and gradual democratization. Section 5 reviews models of dynamic games in resource exploitation involving regime shifts and thresholds. Section 6 reviews some studies of regime shifts in industrial organization theory, with focus on R&D races, including efforts to sabotage rivals in order to prevent entry. Section 7 reviews games of regime shifts when players can manage a Big Push. Section 8 discusses some directions for future research.
Keywords: C00; C70; 330; regime shifts; thresholds; tipping points; political repression; democratization